PARTISIPASI MAHASISWA DI ERA KEMAJUAN TEKNOLOGI INFORMASI KOMUNIKASI: STUDI PEMILIHAN RAYA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU TAHUN 2020 - Muflikhatus Solikha; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The FISIP UNRI online election is the first election for the governor and deputy governor of FISIP UNRI students to be carried out by way of online voting. Compared to FISIP UNRI online election 2018 FISIP UNRI online election 2020 shows a higher level of participation. Even though the e-voting system is still relatively new and the system still has a low level of credibility. Therefore, the author is interested in studying further with the formulation of the problem "How Does the Advancement of Information and Communication Technology Influence Student Political Participation in the 2020 General Election of the Faculty of Social and Political Sciences, University of Riau?" This study aims to describe the Effect of Advances in Information and Communication Technology on Student Political Participation in the General Elections of the Faculty of Social and Political Sciences, University of Riau in 2020. This research is a type of descriptive research using a quantitative approach. The data collection technique in this study used an online survey technique by taking a sample of 97 people from FISIP students at the University of Riau, the margin of error was 10%, the data analysis used was quantitative analysis. The results of the study can be concluded that the results of each indicator question on the use of social media as a means of student political participation in FISIP UNRI online election in 2022 show almost all descriptive results of high participation. That is, it can be concluded that there is a relationship between progress in information and communication technology and student political participation in the 2020 general election of the Faculty of Social and Political Sciences, University of Riau. Keywords: Information and Communication Technology, Political Participation and FISIP UNRI online election.